2021
DOI: 10.1186/s12891-021-04226-4
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical restoration during total hip arthroplasty is related to change in gait pattern - a study based on computed tomography and three-dimensional gait analysis

Abstract: Background The effect of change in hip anatomy on change in gait pattern is not well described in current literature. Therefore, our primary aim was to describe and quantify changes in hip geometry and gait pattern 1 year after total hip arthroplasty (THA) in individuals with hip osteoarthritis. Our secondary aim was to explore the effect of postoperative change in femoral neck anteversion (FNA) and femoral offset and acetabular offset (FO/AO) quota on postoperative change in hip rotation and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 41 publications
1
14
0
2
Order By: Relevance
“…We found no significant difference in cadence postoperatively compared to controls suggesting that the slower walking speed is caused entirely by the shorter stride length. Previous studies, including four systematic reviews, 9,25–27 reported similar consistent results for walking speed and stride length 28–31 . Only one study in a rather small cohort ( N = 12 per group) found a faster walking speed in patients after THA compared to controls 32 .…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…We found no significant difference in cadence postoperatively compared to controls suggesting that the slower walking speed is caused entirely by the shorter stride length. Previous studies, including four systematic reviews, 9,25–27 reported similar consistent results for walking speed and stride length 28–31 . Only one study in a rather small cohort ( N = 12 per group) found a faster walking speed in patients after THA compared to controls 32 .…”
Section: Discussionmentioning
confidence: 63%
“…Previous studies, including four systematic reviews, 9,25-27 reported similar consistent results for walking speed and stride length. [28][29][30][31] Only one study in a rather small cohort (N= 12 per group) found a faster walking speed in patients after THA compared to controls. 32 The reports on cadence are more heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…Cassidy et al reported a significantly low score in the postoperative WOMAC physical function test in a decreased femoral offset group 2 . Conversely, Esbjörnsson et al reported that pain and quality of life were improved, and Bonnin et al reported that the stress of the abductor muscles decreased when the acetabular component was placed slightly medially and the FO was enlarged 3 , 4 . Most of these reported outcomes are based on plain radiographs, which do not show the effects of hip internal and external rotation on FO 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, external hip adduction moments, reflective of internal abduction moments including torques generated by the hip abductor muscles, 24 are of particular interest. With recent studies highlighting the effects of changes in hip geometry on postoperative gait patterns in total hip arthroplasty patients, 25 there is a need to explore whether femoral nailing after ITF influences gait biomechanics. This paper aimed to: (1) identify changes in gait biomechanics after femoral nailing of ITFs between 6 weeks, and 6 months postoperatively; (2) identify differences in gait biomechanics between ITF patients and elderly controls; and (3) to investigate whether FOS and lateral lag screw protrusion (LSP) was correlated with contralateral pelvic drop, maximum external hip adduction moment, step length and gait speed from gait analysis.…”
Section: Introductionmentioning
confidence: 99%